2008
DOI: 10.1002/mrd.20864
|View full text |Cite
|
Sign up to set email alerts
|

Multiple vitellogenin‐derived yolk proteins in gray mullet (Mugil cephalus): Disparate proteolytic patterns associated with ovarian follicle maturation

Abstract: Disparate proteolytic patterns of yolk proteins, derived from three types of vitellogenin (VgA, VgB, and VgC), were observed in gray mullet. Immuno-biochemical analyses of extracts obtained from vitellogenic ovaries (VO) and ovulated eggs (OE) confirmed that a large proportion of VgA-derived lipovitellin (LvA) was degraded into free amino acids (FAAs) during ovarian follicle maturation. The maturation-associated alteration of VgB-derived Lv (LvB) involved only limited proteolysis; the heavy and light LvB chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 34 publications
0
32
1
Order By: Relevance
“…Vtg subtypes has been developed, establishing an assessment system that fully considers the 'multiple Vtg model' mentioned above [118]. Furthermore, in red lip mullet, we established identification and measurement systems for major Vtg subtypes and confirmed estrogen responsiveness.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Vtg subtypes has been developed, establishing an assessment system that fully considers the 'multiple Vtg model' mentioned above [118]. Furthermore, in red lip mullet, we established identification and measurement systems for major Vtg subtypes and confirmed estrogen responsiveness.…”
mentioning
confidence: 76%
“…This is particularly true for Salmonidae. In addition, in fish species where the complete form of Vtg has been further classified into VtgAa and VtgAb, the ratio of subtypes present in the blood depends on each species [117,118]. Because of the large molecular weight differences, the ratio of complete to incomplete forms of Vtg can be readily determined by electrophoresis and similar methods.…”
Section: Applications Of Vitellogenin As Biomarkers For Detection Of mentioning
confidence: 99%
See 1 more Smart Citation
“…This outcome is reasonable because it has been shown that the quantitative ratio of VtgAa versus VtgAb in post-vitellogenic oocytes may possibly control the yield of FAAs (e.g., see Amano et al, 2008a).…”
Section: Nomentioning
confidence: 94%
“…lipovitellin/phosvitin were described during oocyte maturation and early embryos in various species, e.g. barfin flounder, Verasper moseri, a marine teleost (Matsubara et al 1999;Sawaguchi et al 2006), red seabream (Pagrus major), another marine teleost and gray mullet (Mugil cephalus) (Amano et al 2008). A substrate pp25 for protein serine/threonine kinases was derived from the precursor of pp43 that is consisting of a portion of the Xenopus VgB1 protein (Xi et al 2003).…”
Section: Pp25 and Phosvitinmentioning
confidence: 99%